Gaining proficiency in the reading module in IELTS: A study on the efforts of Bangladeshi students - Chowdhury, Sabrina Ahmed (Dhaka University Journal of Linguistics, 2010)
As the name implies, the International English Language Testing System (IELTS) is a test for ascertaining an examinee's English language proficiency. This test is very important for students who want to get admitted to universities or training programmes in English speaking countries. IELTS has four modules including a module on reading. This module gives rise to a number of specific problems for Bangladeshi candidates. The present article attempts to identify the nature and extent of these problems with emphasis on why the examinees find reading module a tough one. The ways and means used by the trainers and teachers to assist Bangladeshi students to overcome these problems have been examined. The article concludes that even with limited resources, the teachers and trainers can follow a number of simple procedures to substantially improve readings skills of students leading to better scores. Key words: IELTS, Language Proficiency, Language Skills DOI: 10.3329/dujl.v2i3.4148 The Dhaka University Journal of Linguistics: Vol.2 No.3 February, 2009 Page: 125-140